Perspectives for an Elko phenomenology using monojets at the 14 TeV LHC - Alves, Alexandre; Dias, Marco André Ferreira Dias; Campos, Fernando Luiz de [UNESP] (World Scientific Publ Co Pte Ltd, 2014)
The aim of this work is to explore the possibility to discover a fermionic field with mass dimension one, the Elko field, in the 14 TeV Large Hadron Collider (LHC), in processes with missing energy and one jet. We explore the possibility of a triple coupling with the Higgs field, generating also a contribution to the Elko mass term, and suggest some possibilities for future studies in this field.
Keywords: Elko phenomenology; Dark matter